Participatory Management for Enhancing Students’ Academic Performance in Public Secondary Schools in Rivers State. - Anna, Ebunu, Akpofure (Advances in Social Sciences Research Journal, 2020)
This study investigated participatory management for enhancing students’ performance in public secondary schools in Rivers State. The study adopted descriptive survey design. The population of the study was all the 276 principals and 8,452 teachers in public senior secondary schools as well as 4,455 students’ parents. The sample of the study was 730 respondents, comprising 90 principals, 360 teachers and 280 parents who were selected through the combination of stratified sampling, simple random sampling and purposive sampling techniques. Instrument of data collection was 10 items questionnaire titled, “Teachers and Parents Participation in Secondary School Management Questionnaire (TPPSSMQ). The instrument was a validated four-point likert styled, Strongly Agree (SA), Agree (A), Disagree (D) and Strongly Disagree (SD). It has a reliability index of 0.82, using Cronbach Alpha Statistical test. The research questions were analysed using mean and standard deviation whereas the hypotheses were tested using z-test statistics at 0.05 alpha level. The findings of the study revealed that the involvement of teachers in school decision-making would give teachers broader opportunity to make inputs in policy issues that concern effective instructional delivery. The study further showed that the involvement of parents in school decision-making would give them ample platform to offer their advices on how to improve the quality of teaching and learning. Based on the findings, the study recommended that school managers should give teachers meaningful opportunities to make inputs, that such opportunities will empower them to take decisions on issues affecting their work performance and productivity for enhanced students’ achievement. Furthermore, school authorities should accord parents’ opportunities to offer their advices on how to enhance resource accountability to foster efficient school management and quality teaching and learning in the school.